Evaluating drivers of spatio-temporal variability in fish fauna of Manasbal Lake of Kashmir Himalayas - Tabasum Yousuf; Saima Andrabi; Shaista Javaid; Sinan Nissar; Yahya Bakhtiyar (Water Science)
Fish populations in aquatic bodies have dropped, possibly due to poor ecological conditions and habitat destruction. This mandates the regular monitoring of the biotic elements and quality of the water bodies for proper management of the resources. The current research examines the relationship between fish abundance and ecological variables in Kashmir’s Manasbal Lake. Three study sites were selected to examine changes in fish abundance caused by various abiotic factors. Following the generalized additive model, the highest fish abundance corresponds to total dissolved solids greater than 150 mg/L, dissolved oxygen greater than 8 mg/L, water temperature greater than 15 °C, alkalinity greater than 135 mg/L, chloride greater than 15 mg/L, nitrate greater than 125 µg/L, total hardness greater than 200 mg/L, low level of total phosphate (100–150 µg/L), and electrical conductivity (200–250 µs/cm). Significant associations between fish composition and abiotic factors were also determined by redundancy analysis (RDA). The initial two axes accounted for 95.6% of the fluctuation of which RDA1 explained 86.63% and was found to be strongly correlated with the variables viz. Nitrate, Nitrite, and TH, while RDA2 explained 8.97% and was found to have a strong positive correlation with free carbon dioxide, alkalinity, total hardness, pH, and electrical conductivity. Sites 1 and 3 were found to be dominated by Crossocheilus diplochilus, Pethia conchonius, and Gambusia holbrooki while Site 2 was dominated by the Schizothorax niger, Schizothorax curvifrons, Carassius carassius, Cyprinus carpio var. communis, and Cyprinus carpio var. specularis.